Early development in the mouth-brooding cichlid fish Satanoperca pappaterra (Perciformes: Cichlidae) - Lopes, Taise M. (2015)
The Neotropical region exhibits the largest diversity of fish worldwide; however, little is known about the early development of fish species from this region. Therefore, to contribute to this knowledge, this study aimed to morphologically describe the early stages of development (eggs, larvae and juveniles) of S. pappaterra using morphometric and meristic traits, and to assess changes in growth rates throughout larval and juvenile development by analyzing the relationships between various morphometric traits using analytical regression models. Both juvenile and adult individuals with mouth-brooded offspring were collected along the basins of the Cuiabá and Manso Rivers in the state of Mato Grosso, Brazil between March 2000 and March 2004. After the adults were identified, the offspring were classified according to its stage (embryonic, larval or juvenile period), and various morphometric and meristic variables were individually measured (when possible). The eggs of this species are yellow in color, oval shaped, show dendritic pigmentation within their yolk, have small to moderately sized perivitelline spaces and lack a mucous membrane and oil droplets. The horizontal and vertical diameters of the sample yolks ranged from 1.43mm to 2.70mm and 1.05mm to 1.68mm, respectively. The standard length of the larval period varied from 4.30mm to 7.16mm, and the standard length of the juvenile period varied from 10.29mm to 24.57mm. Larvae exhibit yolk sacs with internal dendritic pigmentation and dark punctate pigmentation in the dorsal and ventral body regions, whereas irregular transverse spots along the flanks are observed during the juvenile period. Adhesive organs are only present during the yolk-sac stage and at the beginning of the flexion stage. The mouth is terminal during all stages of development. The myomere number varied from 22 to 29 (9 to 16 pre-anal and 10 to 16 post-anal), and the maximal numbers of fin rays and spines were as follows: dorsal, XVI+10; anal, IV+8; pectoral, 16; and pelvic, I+8. Growth analyses identified periods of important change in larval morphology (i.e., metamorphosis), particularly during the flexion and post-flexion stages and in juveniles. Therefore, the morphological development of S. pappaterra is consistent with the ecological requirements of this species, which primarily occurs in structured lentic environments with aquatic macrophytes.  Taise Miranda Lopes1, Fernando Garcia de Oliveira1, Andréa Bialetzki1,2 & Angelo Antonio Agostinho1,21.         Universidade Estadual de Maringá (UEM), Departamento de Biologia (DBI), Programa de Pós-Graduação em Ecologia de Ambientes Aquáticos Continentais (PEA), Av. Colombo, 5790, CEP 87020-900, Maringá, Paraná, Brazil; taisemlopes@gmail.com, fgoliveira.bio@gmail.com2.         Núcleo de Pesquisa em Ictiologia, Limnologia e Aquicultura (NUPELIA), Av. Colombo, 5790, Bloco H90, CEP 87020-900, Maringá, Paraná, Brazil; bialetzki@nupelia.uem.br, agostinhoaa@nupelia.uem.br